Chemical composition and physical characteristics of clones of the ume (Prunus mume siebold et zucc.) - de Mendonça, Veridiana Zocoler [UNESP]; Daiuto, Érica Regina [UNESP]; Caetano, Priscilla Kárim [UNESP]; Vieites, Rogério Lopes [UNESP]; De Carvalho, Lidia Raquel [UNESP]; Smith, Robert E. (Bentham Science Publishers, 2016)
Background: The umê (Prunus mume Siebold et Zucc.) or Chinese plum is used to prepare many food products and is used in traditional medicine. Methods: In this study, 26 clones grown in the Jundiaí do Centro de Frutas do Instituto Agronômico (IAC), in São Paulo, Brazil were analyzed. The fruits from each clone were placed in polystyrene trays, wrapped in polyvinyl chloride film and stored at 8 oC for 21 days. Portions of each sample were collected every three days and analyzed for weight loss and yield of pulp, as well as ascorbic acid, total soluble solids, titratable acidity, pH and colors of the pulp and peel. Results: The results were submitted to principal component analysis by dividing the clones into four groups. Clones 6 and 18 produced the most pulp, while clone 3 had the lowest respiratory activity. Clones 13 and 15 had intermediate respiratory activity when compared to the others. However, they did not lose as much weight during storage. Clones 15 and 1 had the largest concentration of ascorbic acid. Conclusion: These results can be used to select the best clones for each commercial application.
Keywords: Chinese plum; Post-harvest; Prunus mume; Refrigerated storage; Umê